A method for grinding and polishing the cross section of a component containing a soft metal structure
Through the use of special grinding throwing cleansing and ultrasonic cleaning techniques in the process of grinding and throwing of component components, the problem of mixed with the position of the soft metal structure is solved, and an efficient and accurate component analysis is achieved.
Patent Information
- Application Number
- CN202111601114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-12-24
AI Technical Summary
When the prior art grinding and casting samples on the cross-section of components, it is easy to cause impurity particles at the soft metal structure to be embedded, affecting the inspection effect.
Adopt a method of cross -sectional grinding and washing method for components containing soft metal structures. Through the steps of epoxy resin seal, SIC abrasive wet grinding, ultrasound cleaning and other steps, use special grinders to remove impurities particles to ensure the cleansing of the section Essence
Effectively remove the impurities particles in the cross section of the component, improve the accuracy and efficiency of analysis, and ensure that there are no mixed with the soft metal area. It is suitable for the ceramic substrate BGA device and the copper bag aluminum wires and other components.
Smart Images

Figure CN114720220B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a grinding and polishing cleaning method for a cross section of a component containing a soft metal structure, belonging to the technical field of removing impurities from solder or soft nonferrous metals. Background Art
[0002] Cross-sectional grinding and polishing of components is one of the most effective in-situ detection methods for checking the internal structure, coating quality and interface bonding state of components, and plays an irreplaceable role in the field of component reliability analysis. Components are diverse in type and complex in structure. When mechanical grinding and polishing are used to prepare cross-sectional samples of the interface of heterogeneous materials inside components, it is easy to cause grinding and polishing materials or debris to accumulate and embed in the soft metal structure of the component cross section, affecting the cross-sectional inspection effect. Typical component structures include ceramic substrate high-lead lead-out package FPGA (Field Programmable Gate Array) devices and copper-clad aluminum lightweight cable crimping terminals. The observed cross-sections of the above two components contain low-hardness high-lead solder or aluminum wire core materials.
[0003] High-reliability FPGA devices for aerospace use a BGA / CCGA lead-out package structure with a ceramic substrate, which is connected to an external high-lead solder ball / solder column array through the internal metal wiring of the ceramic substrate for lead-out. The solder balls / solder columns are made of high-lead solder (Pb90Sn10, Pb95Sn5, etc.). In order to evaluate the rationality of the device structure and process reliability, the grinding and polishing method is often used to perform cross-sectional sample preparation inspection on the device to analyze the internal structure and solder joint quality of the device. When performing sample preparation inspection along the cross-sectional direction of the substrate-high-lead solder joint, the ceramic substrate and the high-lead solder joint need to be ground and polished at the same time. Due to the large difference in hardness between the ceramic substrate and the high-lead solder joint material on its surface, hard debris such as ceramic substrate debris and grinding and polishing particles will be embedded in the soft high-lead solder; when the debris is seriously embedded, it is impossible to obtain a clean solder joint profile for subsequent analysis and research.
[0004] Copper-clad aluminum composite conductors are made by coating aluminum cores with pure copper strips, and then undergoing copper strip welding, billet drawing, and annealing. Compared with pure copper core conductors, copper-aluminum composite conductors combine the excellent electrical conductivity of copper with the light weight and low cost of aluminum. Especially as conductors in high-frequency signal transmission, the transmission performance is almost the same as that of copper conductors by utilizing the skin effect of conductors, thus achieving the purpose of reducing the cost of raw materials for conductors and reducing the weight of conductors. In the field of aerospace, using copper-clad aluminum conductors to reduce the weight of cables is also of great significance for increasing the payload of aircraft and spacecraft, and various countries have carried out relevant research and applications. During use, aluminum and its oxides have poor weldability, and copper-aluminum conductors are generally assembled by crimping. Due to the large difference in electrode potential between copper and aluminum, the negatively charged aluminum core is prone to galvanic corrosion when encountering corrosive media. Therefore, in high-reliability applications, in order to avoid corrosion of the aluminum core and improve the life and reliability of the crimping terminals, special contact terminals are required to seal and crimp the copper-clad aluminum conductors. In the copper-clad aluminum lightweight cable crimping terminal, there is a copper / silver / aluminum multi-metal crimping interface. Due to the obvious difference in hardness between different metals, after the cross-sectional structure is polished and cleaned using conventional methods, a large amount of impurities will be embedded in the softest aluminum wire core and are difficult to remove, affecting the subsequent analysis of the wire core crimping state and strain. Summary of the invention
[0005] The technical problem solved by the present invention is: to overcome the shortcomings of the prior art and propose a method for grinding and polishing the cross-section of components containing soft metal structures, which has good wetting properties for the grinding and polishing samples. When this cleaning agent is used to clean the cross-section of relevant samples after grinding and polishing, it can effectively remove impurity particles embedded in the cross-sectional structures of high-lead solder, soft non-ferrous metals, etc., to obtain clean component cross-sectional samples, solve the problem of the soft metal structure position cross-sectional embedding affecting the inspection effect, and improve the accuracy and efficiency of related tests.
[0006] The solution of the present invention is:
[0007] A method for grinding and polishing the cross section of a component containing a soft metal structure, comprising:
[0008] S1. Use epoxy resin to potting the sample components, and after the resin is cured, cut the sample close to the surface to be observed;
[0009] S2. Use 320-400 mesh SiC abrasive wet sandpaper for the first step of grinding, grinding the sample to about 0.2-0.5 mm from the cross section of the component to be observed;
[0010] S3. Use wet sandpaper with SiC abrasives of (2-3)N mesh and (4-6)N mesh to grind in the second and third steps respectively, and put the ground samples into L1 grinding and polishing cleaning agent for ultrasonic cleaning; the cleaned samples are inspected under a metallographic microscope. If there are no abrasives or ceramic debris with the corresponding sandpaper particle size embedded in the soft metal area of the component cross section, the cleaning effect is good; if the cleaning effect is not achieved, repeat the L1 grinding and polishing cleaning agent grinding and cleaning, ultrasonic cleaning and inspection operations for 30 seconds until a good cleaning effect is achieved; after the third step of grinding, the component cross section to be observed should be reached;
[0011] S4. Use alumina suspension or diamond suspension with a particle size of 3μm and 1μm in turn, and use a polishing cloth to polish the ground sample in the first and second steps; and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning; the cleaned sample is inspected under a metallographic microscope, and the cleaning effect is good if there is no corresponding polishing particles embedded in the soft metal area; if the cleaning effect is not achieved, repeat the 30s L2 grinding and polishing cleaning agent polishing cleaning, ultrasonic cleaning and inspection operations until a good cleaning effect is achieved;
[0012] S5. Use alumina sol or silica sol polishing liquid with a particle size of 0.02-0.1um, use a polishing cloth to polish the sample in the third step, and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, use a high-pressure air gun to blow dry the sample or wipe it dry with lens paper.
[0013] Furthermore, in S1, when the sample is cut close to the surface to be observed, the tool speed is 2000-3000 r / min, and the tool feed speed is: the tool feed speed of metal material is not more than 3 mm / min, and the tool feed speed of ceramic material is not more than 1 mm / min.
[0014] Furthermore, the mass percentage of L1 polishing cleaning agent is: 70% to 85% of deionized water, 15% to 30% of anhydrous ethanol, 0.1 to 0.3% of Tween 40, 0.05 to 0.15% of OP20, and 0.05 to 0.25% of dodecyl betaine.
[0015] Furthermore, the mass percentage of L2 polishing cleaning agent is: 60% to 70% deionized water, 30% to 40% anhydrous ethanol, 0.1 to 0.2% Tween 40, 0.1 to 0.2% Tween 20, 0.05 to 0.15% OP10, and 0.05 to 0.1% dodecyl betaine.
[0016] Furthermore, in S2, tap water is added to the center area of the grinding disc during grinding, and the sandpaper brand number is recorded as N; the sample grinding pressure is set to 15-25 kPa, the grinding disc speed is 200-300 r / min, and the sample tray speed is 20-40 r / min in the opposite direction of the grinding disc.
[0017] Furthermore, in S3, tap water flow is added to the center area of the grinding disk during grinding, the sample grinding pressure is set to 12-18 kPa, the grinding disk speed is 160-240 r / min, the sample tray speed is 30-60 r / min in the opposite direction of the grinding disk, and each grinding process requires the removal of scratches left by the previous grinding. In the last 30 seconds of the two-step grinding, L1 grinding and polishing cleaning agent is used instead of tap water as the cleaning medium.
[0018] Furthermore, in S4, the sample polishing pressure is set to 10-16 kPa, the polishing disc speed is 180-240 r / min, the sample tray speed is 40-60 r / min in the opposite direction of the polishing disc, and the last 30 seconds of the two-step polishing is cleaned with L2 polishing cleaning agent.
[0019] Furthermore, in S5, the sample polishing pressure is set to 12-18 kPa, the polishing disc speed is 240-300 r / min, the sample tray speed is 40-60 r / min in the opposite direction of the polishing disc, and the last 30 s of polishing is cleaned with L2 polishing cleaning agent.
[0020] The beneficial effects of the present invention compared with the prior art are:
[0021] (1) The present invention can effectively remove the embedded particles and debris in the aluminum wire core with the lowest hardness, facilitate the metallographic inspection of the interface bonding state of the crimped terminal, and provide high-quality non-embedded prefabricated samples for EBSD related analysis;
[0022] (2) The present invention can effectively remove impurity particles embedded in the cross-section of components containing soft metal structures such as high-lead solder joints of BGA devices on ceramic substrates, aluminum wire cores of copper-clad aluminum wire crimping terminals, etc., thereby improving the efficiency and accuracy of analysis;
[0023] (3) The present invention uses a cleaning agent that has good wetting properties on the interface between polishing embedded particles and soft metals, and combines it with the polishing sample preparation process to clean the cross-section of components containing soft metal structures during polishing sample preparation, thereby solving the problem of soft metal embedded in the cross-section of components affecting the analysis effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the metallographic morphology of the BGA solder joint cleaned with a cleaning agent;
[0025] Figure 2This is the SEM morphology of the BGA high-lead solder joint cleaned with a cleaning agent;
[0026] Figure 3 The contact angle between the cleaning agent and high-lead solder;
[0027] Figure 4 It is the processing status of the sample grinding stage;
[0028] Figure 5 This is the sample processing state at the fine polishing stage;
[0029] Figure 6 It is the cleaning effect of the cleaning agent on the cross-section of the copper-clad aluminum wire crimping terminal. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the embodiments.
[0031] A method for grinding and polishing the cross section of a silver-copper-aluminum crimp terminal, comprising:
[0032] S1. Use epoxy resin to potting the sample components. After the resin is cured, the sample can be cut close to the observation surface by mechanical cutting with a diamond blade to reduce the workload of grinding and polishing. When cutting, the speed should be reasonably controlled at 2000-3000r / min and the feed speed should be ≤3mm / min for metal materials and ≤1mm / min for ceramic materials to avoid excessive deformation of the metal or cracking of the ceramic substrate.
[0033] S2. Use 320-400 mesh SiC abrasive wet sandpaper for the first step of grinding. Add tap water to the center of the grinding disc during grinding, and record the sandpaper brand number as N. Set the sample grinding pressure to 15-25 kPa, the grinding disc speed to 200-300 r / min, the sample tray speed to 20-40 r / min in the opposite direction of the grinding disc, and grind the sample to about 0.2-0.5 mm from the cross section of the component to be observed.
[0034] S3. Use wet sandpaper with SiC abrasives of (2-3)N mesh and (4-6)N mesh to grind the second and third steps respectively. Add tap water to the center of the grinding disc during grinding. Set the sample grinding pressure to 12-18kPa, the grinding disc speed to 160-240r / min, and the sample tray speed to 30-60r / min in the opposite direction of the grinding disc. Each grinding process needs to remove the scratches left by the previous grinding. In the last 30s of the two-step grinding, use L1 grinding and polishing cleaning agent instead of tap water as the cleaning medium, and put the ground sample into L1 grinding and polishing cleaning agent for ultrasonic cleaning.
[0035] After cleaning, the sample is inspected under a metallographic microscope. If there are no abrasives or ceramic debris with the corresponding sandpaper particle size in the soft metal area of the component cross section, the cleaning effect is good. If the cleaning effect is not achieved, it is necessary to repeat the L1 grinding and polishing cleaning agent grinding and cleaning, ultrasonic cleaning and inspection operations for 30 seconds until a good cleaning effect is achieved. After the third step of grinding, the cross-section position of the component to be observed should be reached.
[0036] S4. Use alumina suspension or diamond suspension with a particle size of 3μm and 1μm in turn, and polish the ground sample in the first and second steps on a short-napped synthetic velvet cloth. Set the sample polishing pressure to 10-16kPa, the polishing disc speed to 180-240r / min, and the sample tray speed to 40-60r / min in the opposite direction of the polishing disc. Use L2 grinding and polishing cleaning agent to clean the last 30s of the two-step polishing, and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, the sample is inspected under a metallographic microscope. If there is no corresponding polishing particle embedded in the soft metal area, the cleaning effect is good; if the cleaning effect is not achieved, repeat the 30s of L2 grinding and polishing cleaning agent polishing cleaning, ultrasonic cleaning and inspection operations until a good cleaning effect is achieved.
[0037] S5. Use alumina sol or silica sol polishing liquid with a particle size of 0.02-0.1um to polish the sample in the third step on a long-napped synthetic artificial velvet polishing cloth. Set the sample polishing pressure to 12-18kPa, the polishing disc speed to 240-300r / min, and the sample tray speed to 40-60r / min in the opposite direction of the polishing disc. Clean with L2 grinding and polishing cleaning agent for the last 30s of polishing, and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, use a high-pressure air gun to blow dry the sample or wipe it dry with lens paper.
[0038] The mass percentage of L1 grinding and polishing cleaning agent is: 70% to 85% of deionized water, 15% to 30% of anhydrous ethanol, 0.1 to 0.3% of Tween 40, 0.05 to 0.15% of OP20, and 0.05 to 0.25% of dodecyl betaine.
[0039] The mass percentage of L2 grinding and polishing cleaning agent is: 60% to 70% of deionized water, 30% to 40% of anhydrous ethanol, 0.1 to 0.2% of Tween 40, 0.1 to 0.2% of Tween 20, 0.05 to 0.15% of OP10, and 0.05 to 0.1% of dodecyl betaine.
[0040] Example 1
[0041] A method for grinding and polishing a cross section of a high-lead solder joint at a lead-out end of a flip-chip FPGA device led out on a ceramic substrate BGA / CCGA, belonging to a method for removing impurities from high-lead solder, comprising the following steps:
[0042] 1) Sample curing and sample preparation stage: Use sample preparation ring to fix the FPGA solder joint to be tested horizontally and then use epoxy resin to pot it. After the resin is cured, a diamond blade can be used to mechanically cut the sample at a speed of 3000r / min and a feed speed of 0.5mm / min to cut it close to the cross section to be observed. About 0.5mm.
[0043] 2) Sample grinding stage processing: Select 400 mesh SiC abrasive wet sandpaper, grind the sample to about 0.2mm from the component to be observed at a grinding pressure of 20kPa, a grinding disc speed of 200r / min, and a reverse sample tray speed of 20r / min; select 1200 mesh and 2400 mesh SiC abrasive wet sandpaper, grind the sample to the component to be observed at a grinding pressure of 15kPa, a grinding disc speed of 240r / min, and a reverse sample tray speed of 60r / min. The sample is ground to the cross section to be observed. The last 30s of the two-step grinding is cleaned with L1 grinding and polishing cleaning agent instead of tap water, and the ground sample is placed in L1 grinding and polishing cleaning agent for ultrasonic cleaning. The cleaned sample is inspected under a metallographic microscope, and there is no abrasive or ceramic debris embedded in the cross section of the high-lead solder joint, as shown in Figure 4.
[0044] 3) Sample rough polishing stage treatment: Select 3μm and 1μm diamond suspensions, and perform the first and second step polishing on the ground samples with a short-haired synthetic velvet cloth. The polishing parameters are 10kPa grinding pressure, 240r / min grinding disc speed, 50r / min reverse sample tray speed, polishing for 150s, and the last 30s of the two-step polishing are cleaned with L2 grinding and polishing cleaning agent, and the polished samples are placed in L2 grinding and polishing cleaning agent for ultrasonic cleaning.
[0045] 4) Sample fine polishing stage processing: Select alumina sol polishing liquid with a particle size of 0.05um, and finely polish and clean the sample on a long-napped synthetic artificial velvet polishing cloth. The polishing parameters are 12kPa grinding pressure, 300r / min grinding disk speed, 60r / min reverse sample tray speed, polishing for 180s, and the last 30s are cleaned with L2 grinding and polishing cleaning agent. The polished sample is placed in L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, the sample is blown dry with a high-pressure air gun or wiped dry with lens paper. The conventional grinding and polishing method and this method are used to compare the effects of grinding and polishing high-lead solder joints on the surface of FPGA. Figure 5 shown.
[0046] Example 2
[0047] A method for grinding and polishing the axial cross section of a copper-clad aluminum lightweight wire crimping terminal, belonging to a method for removing impurities from soft nonferrous metals, comprises the following steps:
[0048] 1) Sample curing and sample preparation stage: After using the sample preparation card to fix the crimped terminal to be tested horizontally along the axial direction, use epoxy resin to pot it. After the resin is cured, a diamond blade can be used to mechanically cut the sample at a speed of 2000 r / min and a feed speed of 2mm / min to cut it close to about 1mm from the cross section to be observed.
[0049] 2) Sample grinding stage processing: Select 400 mesh SiC abrasive wet sandpaper, grind the sample to about 0.5mm from the cross section of the component to be observed at 20kPa grinding pressure, 200r / min grinding disc speed, 40r / min reverse sample tray speed; select 1200 mesh and 2400 mesh SiC abrasive wet sandpaper, grind the sample to the cross section of the component to be observed at 12kPa grinding pressure, 160r / min grinding disc speed, 30r / min reverse sample tray speed, and grind the sample to the cross section of the component to be observed. In the last 30s of the two-step grinding, use L1 grinding and polishing cleaning agent instead of tap water for cleaning, and put the ground sample into L1 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, the sample was inspected under a metallographic microscope, and there was no abrasive embedded in the cross section of the aluminum wire core, as shown in Figure X.
[0050] 3) Sample rough polishing stage treatment: Select 3μm and 1μm diamond suspensions, and perform the first and second step polishing on the ground samples with a short-nap synthetic velvet cloth. The polishing parameters are 16kPa grinding pressure, 180r / min grinding disc speed, 60r / min reverse sample tray speed, polishing for 120s, and the last 30s of the two-step polishing is cleaned with L2 grinding and polishing cleaning agent, and the polished samples are placed in L2 grinding and polishing cleaning agent for ultrasonic cleaning.
[0051] 4) Sample fine polishing stage: Select a mixed polishing liquid of 0.05um alumina sol and 0.02um silica sol with a particle size of 0.05um, and use a long-napped synthetic rayon polishing cloth to fine-polish and clean the sample. The polishing parameters are 18kPa grinding pressure, 300r / min grinding disc speed, 40r / min reverse sample tray speed for polishing for 150s, and the last 30s for cleaning with L2 grinding and polishing cleaning agent. The polished sample is then placed in L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, the sample is dried with a high-pressure air gun or wiped dry with lens paper. The effects of grinding and polishing the axial section of the copper-clad aluminum wire crimping terminal using conventional grinding and polishing methods and this method are compared. Figure 6 shown.
[0052] Figure 1 The metallographic morphology of the BGA device solder joints on a ceramic substrate prepared by polishing and cleaning using this patented cleaning agent shows that there are no large-sized ceramic debris embedded in the high-lead solder, and no obvious oxidation discoloration occurs in the solder area. Figure 2This is the SEM morphology of the local area of the high-lead solder in the solder joint. A small amount of diamond embedded in the solder does not cause serious local deformation of the solder joint. The distribution of lead-rich phase and tin-rich phase can be effectively distinguished in the solder area, and a good observation effect can be achieved for the solder joint.
[0053] Figure 3 The metallographic morphology of the copper-clad aluminum wire crimping terminal prepared by grinding and polishing using this patented cleaning agent is shown in this paper. This method can effectively remove the embedded particles and debris in the aluminum wire core with the lowest hardness, facilitate the metallographic inspection of the interface bonding state of the crimping terminal, and provide high-quality non-embedded prefabricated samples for EBSD related analysis.
[0054] The test results show that the method shown in this patent can effectively remove impurity particles embedded in the cross-section of components containing soft metal structures, such as high-lead solder joints of BGA devices on ceramic substrates, aluminum wire cores of copper-clad aluminum wire crimp terminals, and improve the efficiency and accuracy of analysis.
[0055] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention is within the scope of the present invention.
Claims
1. A method for grinding and polishing the cross section of a component containing a soft metal structure, characterized in that the steps include: S1. Use epoxy resin to potting the sample components, and after the resin is cured, cut the sample close to the surface to be observed; S2. Use 320-400 mesh SiC abrasive wet sandpaper for the first step of grinding, grinding the sample to 0.2-0.5 mm away from the cross section of the component to be observed; When grinding, add tap water flow to the center of the grinding disc, record the sandpaper brand number as N; set the sample grinding pressure to 15-25kPa, the grinding disc speed to 200-300r / min, and the sample tray speed to 20-40r / min in the opposite direction of the grinding disc; S3. Use wet SiC abrasive sandpaper with a mesh size of 2-3N and 4-6N to grind the second and third steps respectively, and put the ground samples into L1 grinding and polishing cleaning agent for ultrasonic cleaning; the cleaned samples are inspected under a metallographic microscope. If there are no abrasives or ceramic debris with a corresponding sandpaper particle size embedded in the soft metal area of the component cross section, the cleaning effect is good; if the cleaning effect is not achieved, repeat the L1 grinding and polishing cleaning agent grinding and cleaning, ultrasonic cleaning and inspection operations for 30 seconds until a good cleaning effect is achieved; after the third step of grinding, the component cross section to be observed should be reached; The mass percentage of L1 polishing cleaning agent is: 70% to 85% deionized water, 15% to 30% anhydrous ethanol, 0.1 to 0.3% Tween 40, 0.05 to 0.15% OP20, and 0.05 to 0.25% dodecyl betaine; S4. Use alumina suspension or diamond suspension with a particle size of 3μm and 1μm in turn, and use a polishing cloth to polish the ground sample in the first and second steps; and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning; the cleaned sample is inspected under a metallographic microscope, and the cleaning effect is good if there is no corresponding polishing particles embedded in the soft metal area; if the cleaning effect is not achieved, repeat the 30s L2 grinding and polishing cleaning agent polishing cleaning, ultrasonic cleaning and inspection operations until a good cleaning effect is achieved; The mass percentage of L2 polishing cleaning agent is: 60% to 70% deionized water, 30% to 40% anhydrous ethanol, 0.1 to 0.2% Tween 40, 0.1 to 0.2% Tween 20, 0.05 to 0.15% OP10, and 0.05 to 0.1% dodecyl betaine; S5. Use alumina sol or silica sol polishing liquid with a particle size of 0.02-0.1um, use a polishing cloth to polish the sample in the third step, and put the polished sample into L2 grinding and polishing cleaning agent for ultrasonic cleaning. After cleaning, use a high-pressure air gun to blow dry the sample or wipe it dry with lens paper.
2. A method for grinding and polishing the cross section of a component containing a soft metal structure according to claim 1, characterized in that: In S1, when the sample is cut close to the surface to be observed, the tool speed is 2000-3000 r / min, and the tool feed speed is: the tool feed speed of metal material is not more than 3 mm / min, and the tool feed speed of ceramic material is not more than 1 mm / min.
3. A method for grinding and polishing the cross section of a component containing a soft metal structure according to claim 1, characterized in that: In S3, tap water was added to the center of the grinding disc during grinding, the sample grinding pressure was set to 12-18 kPa, the grinding disc speed was 160-240 r / min, and the sample tray speed was 30-60 r / min in the opposite direction of the grinding disc. Each grinding process required the removal of scratches left by the previous grinding. In the last 30 seconds of the two-step grinding, L1 polishing cleaning agent was used instead of tap water as the cleaning medium.
4. A method for grinding and polishing the cross section of a component containing a soft metal structure according to claim 1, characterized in that: In S4, the sample polishing pressure is set to 10-16 kPa, the polishing disc speed is 180-240 r / min, the sample tray speed is 40-60 r / min in the opposite direction of the polishing disc, and the last 30 seconds of the two-step polishing is cleaned with L2 polishing cleaning agent.
5. A method for grinding and polishing the cross section of a component containing a soft metal structure according to claim 1, characterized in that: In S5, the sample polishing pressure is set to 12-18 kPa, the polishing disc speed is 240-300 r / min, the sample tray speed is 40-60 r / min in the opposite direction of the polishing disc, and the last 30 s of polishing is cleaned with L2 polishing cleaning agent.
Citation Information
Patent Citations
Polishing solution for inhibiting electrochemical corrosion of phase change material
CN102516879A
Preparation method of electronic back scattering diffraction sample of tin-based solder interconnecting welding spot
CN108061737A